Cinema beyond aesthetics analyses on the aestheticization of violence and abjection in the cinema of Brillante Mendoza - Gonzales, Dane Anthony M.; Quintos, Jay Jomar F. (2018)
The researcher explored the cinema of Brillante Mendoza as one of the face of Philippine Independent New Wave Cinema. His films are often portrayed the quotidian lives of Filipino people and themes of violence in society. The study analyzes the aesthetics of violence and abjection among the 14 films of Brillante Mendoza (2005-2016). Using the textual analysis, the movies are interpreted on how it uses the elements of cinema, such as the mise-en-scene, and sound design. The study also focuses on four categories of violence: Subjective/Direct Violence, Structural Violence, Cultural Violence, and Systematic Violence. The analyses are all grounded by the critical theory of abjection by Julia Kristeva. The theory correlates to the portrayal of violence which emphasizes the abject that disturbs the identity, system, and symbolic social order. It also suggests that abjection can explain the structural and political acts of inclusion/exclusion in our society. The results exhibit Mendoza?s competence and expertise in terms of their plasticity and aesthetics. In relation to violence and abjection, his choice of aesthetics emphasized the vulnerability and mortality of human bodies. To aestheticize the considered abject of society or the excluded characters, Mendoza depicts their struggles and suffering using the cinematic elements. Several of his films also portrayed aspects of culture that legitimize certain acts of violence and purify the perpetrators of violence. To aestheticize violence and abjection, Mendoza obediently follows the existing social order and accepts the oppressive system in our society. Since aesthetics is the main priority in his portrayal of violence and abjection, the implication creates a gap to engage with significant social issues in the scenes of his films.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2018